Endocrine and paracrine characteristics of neuroendocrine prostate cancer - Arman, Tarana; Nelson, Peter S. (Frontiers in Endocrinology, 2022)
Prostate cancer is a common malignancy affecting men worldwide. While the vast majority of new-ly diagnosed prostate cancers are categorized as adenocarcinomas, a spectrum of uncommon tumor types occur including those with small cell and neuroendocrine cell features. Benign neuroendo-crine cells exist in the normal prostate microenvironment, and these cells may give rise to primary neuroendocrine carcinomas. However, the more common development of neuroendocrine prostate cancer is observed after therapeutics designed to repress the signaling program regulated by the androgen receptor which is active in the majority of localized and metastatic adenocarcinomas. Neuroendocrine tumors are identified through immunohistochemical staining for common markers including chromogranin A/B, synaptophysin and neuron specific enolase (NSE). These markers are also common to neuroendocrine tumors that arise in other tissues and organs such as the gas-trointestinal tract, pancreas, lung and skin. Notably, neuroendocrine prostate cancer shares bio-chemical features with nerve cells, particularly functions involving the secretion of a variety of pep-tides and proteins. These secreted factors have the potential to exert local paracrine effects, and dis-tant endocrine effects that may modulate tumor progression, invasion, and resistance to therapy. This review discusses the spectrum of factors derived from neuroendocrine prostate cancers and their potential to influence the pathophysiology of localized and metastatic prostate cancer.